LIP Prints Patterns: A Study among the Aryan and Dravidian Ethnic Population in India- A Cross Sectional Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Lip prints are subjected to be unique for all the individuals except monozygotic twins; hencethey can be an important indicator for human identification. Since, Aryan population are descendants ofnorth India and Dravidian population are descendants of south India. AIM: The aim of the study was toassess the uniqueness of lip prints among Aryan and Dravidian ethnic population. Materials and method: Across sectional study was conducted among 192 individuals of Aryan and Dravidian population. Convenientsampling was used to select the study population among the Tamilnadu and Chandigarh states in India. Thelip prints were recorded with the help of lip sticks and glue portion of the cello tape. Statistical analysiswas done using spss software version 20.0. Results: In the present study, branched lip print pattern waspredominantly seen in males of Dravidian population. In contrast, least commonly predominant was partiallyvertical pattern which was absent in both the males and females of Aryan population. Conclusion: Lip printsare a unique feature for human identification. In this study, it was found that branched lip print pattern washigher in males of Dravidian population and the partially vertical type was least predominant among themales and females of Aryan and Dravidian population.